Effectiveness of Differentiated Learning Strategies to Reduce Some of the Difficulties Associated with Developmental Motor Synergy (Dyspraxia) for Learning Disabilities Students - Ramadan Zahran, Ayman; Hamyer Almalek, Mahra (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed to verify the effectiveness of applying a differentiated learning strategy to reduce some of the difficulties associated with developmental motor disorder (dyspraxia) among a sample of (25) students with academic and developmental learning disabilities at the American Academy of Ras Al Khaimah, in the Emirate of Ras Al Khaimah at UAE, their ages ranged between (4) - 7) years, who were diagnosed as suffering from a developmental motor syndrome disorder according to the questionnaire of the developmental motor disorder that was prepared by Khasawneh and Khawaldeh (2016), the study depended on the semi-experimental approach based on the one group and the application pre and post, researchers prepared test for the difficulties associated with the developmental motor disorder (dyspraxia), which included three axes: verbal communication, reading and attention. Findings of the study indicated that there are statistically significant differences between the average scores for the applications before and after in favor of post-implementation in the three axes, which indicated the effectiveness of strategies like differentiated learning in alleviating some of the difficulties associated with dyspraxia in those with academic and developmental learning difficulties.